An experimental investigation for pullout response of a single granular pile anchor in clayey soil - Hans Raj Vashishtha (SpringerOpen, 2021)
Abstract The granular pile anchor foundation is an effective and economical foundation system to counter the pullout forces exerted in case of transmission towers or foundations in expansive soil. The pullout tests were performed to study the behaviour of a single granular pile anchor in the clayey soil bed. Tests were conducted in a steel tank of 1 ×  1  ×  1 m size with the help of loading frame arrangement. The pullout load required for upward movement equal to 10% diameter was considered as the pullout capacity of the granular pile anchor. In the parametric study, length and diameter of the granular pile anchor were varied to examine their effect. Number of anchor plates was also varied in few tests. The pullout capacity enhanced with an increase in the diameter and length to diameter ratio. The effect of the length to diameter ratio was appreciable up to the value of 10. However, no significant effect was found in the cases of multiple anchor plates. A relationship is proposed to predict normalized pullout capacity.